15‐LO/15‐HETE Mediated Vascular Adventitia Fibrosis via p38 MAPK‐Dependent TGF‐β. Issue 2 (25th October 2013) - Zhang, Li; Li, Yumei; Chen, Minggang; Su, Xiaojie; Yi, Dan; Lu, Ping; Zhu, Daling
Abstract 15‐Lipoxygenase/15‐hydroxyeicosatetraenoic acid (15‐LO/15‐HETE) is known to modulate pulmonary vascular medial hypertrophy and intimal endothelial cells migration and angiogenesis after hypoxia. However, it is unclear whether 15‐HETE affects the adventitia of the pulmonary arterial wall. We performed immunohistochemistry, adventitia fibrosis, pulmonary artery fibroblasts phenotype and extracellular matrix (ECM) deposition to determine the role of 15‐HETE in hypoxia‐induced pulmonary vascular adventitia remodeling. Our studies showed that O2 deprivation induced adventitia hypertrophy of pulmonary arteries with ECM accumulation in both humans with pulmonary arterial hypertension and hypoxic rats. Hypoxia induced 15‐LO expression in adventitia. With the inhibitor, NDGA depressed the hypoxia induced ECM deposition and 15‐LO production in hypoxic rats. Hypoxia up‐regulated the expression of α‐SMA, type‐Ia collagen and fibronectin in cultured fibroblasts, which seemed to be due to the increased 15‐LO/15‐HETE. Exogenous 15‐HETE mediated the ECM and phenotypic alterations of the fibroblasts as well. The 15‐LO/15‐HETE induced adventitia fibrosis and fibroblasts phenotypic alterations depended on signaling of the transforming growth factor‐β1 (TGF‐β1)/Smad2/3 pathway. P38 mitogen‐activated protein kinase (p38 MAPKs) was likely to mediate 15‐LO induced TGF‐β1 and Smad2/3 activation after hypoxia. The results suggest that adventitia fibrosis is an important event in the hypoxia induced pulmonary arterial remodeling, which relies on 15‐LO/15‐HETE induced p38 MAPK‐dependent TGF‐β1/Smad2/3 intracellular signaling systems. J. Cell. Physiol. 229: 245–257, 2014. © 2013 Wiley Periodicals, Inc.